PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM @IBUPEDIA_ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PARENTING ( SURVEI PADA FOLLOWERS INSTAGRAM @IBUPEDIA_ID - Anggun Herawati, Anggun; Danang Tandyonomanu (Universitas Negeri Surabaya, 2025)
The phenomenon of increased social media usage in Indonesia, particularly Instagram, has brought about significant changes in the way individuals access information. One area that has received great attention is parenting, with Instagram accounts such as ibupedia_id having more than 1.4 million followers as of August 2024. This study aims to analyze the effect of using Instagram ibupedia_id on fulfilling parenting information needs. Using a descriptive quantitative approach, 400 respondents were selected through purposive sampling. Data was collected using the G-Form which measures social media usage variables (context, communication, collaboration, connection) and information needs (current, everyday, exhaustive, catching-up need approach). The analysis was conducted using a simple linear regression test showing a significant effect with a significance value of 0.00 <0.05. The results of the analysis show that the use of Instagram ibupedia_id has a significant influence on the fulfillment of parenting information needs, with a calculated t value of (9.873) which is greater than the t table(1.966). This study provides theoretical contributions by strengthening the theory of information seeking behavior (Wilson) in the context of social media, as well as practical benefits for social media account managers in strategizing content that better suits the needs of their audience.